Baihe Zhimu formula attenuates the efficacy of tamoxifen against breast cancer in mice through modulation of CYP450 enzymes - Hailong Li; Chunyu Wu; Yu Liu; Shuo Zhang; Xiufei Gao (BMC, 2019)
Abstract Background Major depression is an important complication in patients with breast cancer, but is an underrecognized and undertreated condition in this population. The Baihe Zhimu Tang (BZ formula) is a traditional Chinese formula consisting of Lilium brownii var. viridulum Baker (L. brownii) and Anemarrhena asphodeloides (A. asphodeloides) Bunge that is used for the treatment of depression. However, the interaction between tamoxifen and BZ formula is frequently overlooked by traditional and alternative medical doctors. In the present study, the influence of BZ formula on the effectiveness of tamoxifen in breast cancer in mice and the effects of tamoxifen on the antidepressant effect of BZ formula and its major components mangiferin and timosaponin BII in mice were investigated. Methods Identification of the major components of BZ formula was performed using fast HPLC-tandem mass spectrometry (HPLC-MS/MS). The main flavonoids and saponins in A. asphodeloides were determined by HPLC-UV and HPLC-ELSD, separately. The antidepressant efficacy of BZ formula was evaluated using a mouse tail-suspension test. The effects of BZ formula on the antineoplastic activity of tamoxifen were performed in a mouse xenograft model of human breast cancer MCF-7 cells. P450 activity was determined using microsomal incubations by HPLC-MS/MS. Measurement of serum concentrations of tamoxifen and its metabolites was used by HPLC-MS/MS. Results BZ formula attenuated the effectiveness of tamoxifen treatment of breast cancer and reduced the concentrations of endoxifen and 4-OH-tamoxifen in tumor-bearing mice. Of two of the major components of BZ formula, the antidepressant effect of mangiferin, but not timosaponin BII, was significantly inhibited by tamoxifen in mice. BZ formula and its component mangiferin also significantly inhibited CYP450 enzyme activity in rat liver microsomes. Conclusion BZ formula attenuated the effectiveness of tamoxifen in treatment of breast cancer in mice by influencing CYP450 enzymes. The present study laid a foundation for the treatment of patients with breast cancer and depression by BZ formula or other Chinese herbal formulas containing A. asphodeloides.